Rhythm, movement, and autism: using rhythmic rehabilitation research as a model for autism - LaGasse, A. Blythe; Hardy, Michelle W. (Frontiers in Integrative Neuroscience, 2013)
Recently, there has been increased focus on movement and sensory abnormalities in autism spectrum disorders (ASD). This has come from research demonstrating cortical and cerebellar difference in autism, with suggestion of early cerebellar dysfunction. As evidence for an extended profile of ASD grows, there are vast implications for treatment and therapy for individuals with autism. Persons with autism are often provided behavioral or cognitive strategies for navigating their environment; however, these strategies do not consider differences in motor functioning. One accommodation that has not yet been explored in the literature is the use of auditory rhythmic cueing to improve motor functioning in ASD. The purpose of this paper is to illustrate the potential impact of auditory rhythmic cueing for motor functioning in persons with ASD. To this effect, we review research on rhythm in motor rehabilitation, draw parallels to motor dysfunction in ASD, and propose a rationale for how rhythmic input can improve sensorimotor functioning, thereby allowing individuals with autism to demonstrate their full cognitive, behavioral, social, and communicative potential.